Deciphering HER2 Breast Cancer Disease: Biological and Clinical Implications - Godoy-Ortiz, Ana; Sanchez-Muñoz, Alfonso; Chica Parrado, Maria Rosario; Álvarez, Martina; Ribelles, Nuria; Rueda Dominguez, Antonio; Alba, Emilio (Frontiers in Oncology, 2019)
The identification of extensive genetic heterogeneity in human breast carcinomas poses a significant challenge for designing effective treatment regimens. Significant genomic evolution often occurs during breast cancer progression, creating variability within primary tumors as well as between the primary carcinoma and metastases. A clear example of this is the HER2 positive breast cancer. The clinical impact of the biological heterogeneity within HER2-positive breast cancer is not fully understood. In these tumors, we can find all of the transcriptional subtypes of breast cancer, even the basal like or luminal A subtypes. While the HER2-enriched subtype is the most representative transcriptional subtype in this tumor, we can find it too in HER2-negative breast cancers. This subtype is characterized by high expression of the HER2 and proliferation gene clusters. Thus, the following hypothesis can be suggested: the HER2 amplification can be a distinct driver event seen in all intrinsic subtypes, rather than a subtype marker, and the HER2-enriched subtype can have a distinctive transcriptional landscape independent of HER2 amplification. In this review, we present an extensive revision about the last highlights and advances in clinical outcomes and genomic features in the HER2-positive breast cancer and the HER2-enriched subtype, in an attempt to improve understanding the underlying biology and the drivers of both entities.